Transcription-induced barriers to supercoil diffusion in the Salmonella typhimurium chromosome - Deng, Shuang (National Academy of Sciences, 2004)
Transcription and replication both influence and are influenced by superhelical changes in DNA. Explaining how supercoil movement is channeled in living chromosomes has been a major problem for 30 years. Transcription of membrane-associated proteins leads to localized hypersupercoiling of plasmid DNA, and this behavior indicates the presence of aberrant supercoil diffusion. Using the lambda Red recombination system, we constructed model domains in the Salmonella typhimurium chromosome to analyze supercoiling dynamics of regions encoding membrane proteins. Regulation of Tn10-derived tetracycline resistance involves a repressor, TetR, and a membrane-bound export pump, TetA. Strains deficient in TetR activity had 60-fold higher transcription levels (from P(A)) than TetR-positive strains. High tetA transcription caused a 10- to 80-fold decrease in the γδ resolution efficiency for the domain that includes the Tet module. Replacing tetA with genes encoding cytosolic proteins LacZ and Kan also caused the appearance of supercoil diffusion barriers in a defined region of the chromosome. In strains containing a functional TetR located next to a regulated lacZ reporter (P(R)tetR-P(A)lacZ), induction of transcription with chlortetracycline caused a 5-fold drop in resolution efficiency in the test domain interval. A short half-life resolvase showed that barriers appeared and disappeared over a 10- to 20-min span. These studies demonstrate the importance of transcription in chromosome structure and the plasticity of supercoil domains in bacterial chromosomes.